A Flexible Multiband Multicarrier Signal Design for Broadband Channel Sounding Applications - Iqbal, A. (Korea Information Processing Society, 2022)
Radio frequency radars have garnered considerable attention in contactless sensing. The congestion in frequency bands and ultra-wideband (UWB) sensing requirements pose challenges to the design of the radars. RF radars can be alternatively considered as channel sounders, which too are facing new channel characterization and modeling challenges owing to new frequency bands in 5th generation (5G) and 6th generation (6G) cellular networks. Various sounding systems were developed to meet the frequency and system bandwidth requirements. However, most offer limited system bandwidth and cannot be easily tuned for different applications. This work aims to address these challenges, by providing a new multiband multicarrier architecture and flexible signal design for channel sounding. Firstly, a channel sounder architecture is developed using commercial software-defined radios (SDRs). Secondly, a new phase-modulated multiband orthogonal frequency division multiplexing (MB-OFDM) waveform, which is designed to provide a flexible frame structure with a low peak-to-average power ratio (PAPR), is proposed to optimize the pulse repetition period for the sounding system by maintaining all the valuable properties of OFDM. The overall system is implemented in a simulated environment, and the results show an improved PAPR performance of the MBOFDM signal design. In addition, the overall system is tested for different channel conditions and validated against theoretical data. The numerical experiments show that the proposed system is a viable option for UWB channel sounding for a wide range of applications Â© 2022. Human-centric Computing and Information Sciences.All Rights Reserved